PERAN BANK DAN PEGADAIAN SYARIAH DALAM PEMENUHAN KEBUTUHAN EKONOMI RUMAH TANGGA - Prihantono Prihantono (The Pontianak State Institute of Islamic Studies, 2014)
Sharia banking and pawn shops play an active role in improving the well-being of society, though only by working to deliver and provide products that are needed by the family and the community widely. It is unfortunate if the financial institution as the institution of intermediation that works by relying on condition of the advantages and disadvantages of the economic factors existing in society are unable to read carefully and take part in connecting and bringing together both of these conditions so that the economic problems in the community as well as the household can be resolved. It would be of course more regrettable if it occurred to a Shariah-compliant financial institution. Household spending patterns of the community with the reality of a considerable number of needs, as well as a relatively small income, often showed a disregard for the economic order in the household economy between the amount of income earned and the amount spent. Therefore, the household economy often suffers from bankruptcy and is forced to enter into the mechanism of a credit scheme.